A Comparison of digestive Tract Morphology in muskoxen and caribou from Victoria Island, Northwest Territories, Canada - Hans Staaland; Jan Z. Adamczewski; Anne Gunn (Rangifer, 1997)
Although caribou and muskoxen coexist in close proximity on southeastern Victoria Island, they appear primarily adapted to different diets and foraging strategies. Visual inspection and analysis of rumen contents for fiber and lignin from the study (unpubl.) also indicate a predominantly graminoid diet in the muskoxen and a more varied diet with a substantial browse component in the caribou.This should reduce the likelihood of competition for limited food resources in winter.